2018
DOI: 10.1021/acsenergylett.8b00273
|View full text |Cite
|
Sign up to set email alerts
|

pH Effects on the Selectivity of the Electrocatalytic CO2 Reduction on Graphene-Embedded Fe–N–C Motifs: Bridging Concepts between Molecular Homogeneous and Solid-State Heterogeneous Catalysis

Abstract: In the past decades, the surplus of atmospheric CO2 concentration has drawn tremendous political and scientific attention for its negative impacts, such as the greenhouse effect and ocean carbonation. To mitigate such CO2 issues, a combination of various strategies is required. The electrochemical CO2 reduction reaction (CO2RR) is a promising alternative to convert CO2 into carbon-based chemicals and fuels, and electricity generated from the renewable sources (solar and wind) could be employed to sustain this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
206
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(236 citation statements)
references
References 63 publications
14
206
1
3
Order By: Relevance
“…Most of the CO2RR studies are carried out in 0.1 M KHCO 3 electrolyte which has a lower buffer capacity resulting in a higher local pH in comparison with KH 2 PO 4 / K 2 HPO 4 buffer. [24] By contrast, the selectivity towards CH 4 is higher than that reported on other MNC catalysts (Table S1). [24] Our results, however, are comparable with those obtained in KH 2 PO 4 /K 2 HPO 4 buffer.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Most of the CO2RR studies are carried out in 0.1 M KHCO 3 electrolyte which has a lower buffer capacity resulting in a higher local pH in comparison with KH 2 PO 4 / K 2 HPO 4 buffer. [24] By contrast, the selectivity towards CH 4 is higher than that reported on other MNC catalysts (Table S1). [24] Our results, however, are comparable with those obtained in KH 2 PO 4 /K 2 HPO 4 buffer.…”
Section: Resultsmentioning
confidence: 62%
“…[13] The activity, however, was dramatically increased by incorporation of a metal to the NÀ C structure. [24] Combined DFT and experimental studies have found that the high binding energy of the FeN x centers towards CO and CO 2 is responsible for the early CO onset potential on FeNC catalyst. Furthermore, the metal center has been shown to have a crucial role on determining the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] We therefore define the applied potential to overcome the maximum energy barriers as the overpotentials (η) for CO 2 RR or HER. [32][33][34] We therefore define the applied potential to overcome the maximum energy barriers as the overpotentials (η) for CO 2 RR or HER.…”
Section: Reaction Pathways and Scaling Relationshipmentioning
confidence: 99%
“…Combined with experimental measurements and DFT calculations, they found that at low overpotential regime (>−0.45 eV), potential‐determining step is the first proton‐coupled electron transfer reduction of CO 2 to adsorbed COOH; at the intermediate overpotential regime around −0.6 Vs RHE, CO turn‐over frequency (TOF) is linearly related to the CO binding energy: stronger CO binding corresponds to higher CO TOF, indicating COOH* → CO* being the rate‐determining step; at large overpotential regime <−0.7 versus RHE, Co‐ and Mn‐based catalysts start to strongly catalyze the hydrogen evolution reaction, while the Ni‐ and Cu‐based catalysts exhibit very weak binding of H* which makes the HER unfavorable and both high CO selectivity and reactivity can be obtained for Ni‐based catalysts. Meanwhile, Varela et al focused on the origin of the pH effects on the selectivity. They found that the CO formation rate is independent of the pH at fixed potential versus NHE, in consistency with a proton‐decoupled electron‐transfer pathway in which the reduction of CO 2 to CO occurs via a CO 2 − * intermediate, suggesting a decoupled elementary proton−electron transfer mechanism (Figure b,c).…”
Section: Co2r Reactionmentioning
confidence: 99%